2019
DOI: 10.1080/15583058.2019.1695155
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Vibrations of Age-old Masonry Towers: Results of Long-term Dynamic Monitoring in the Historic Centre of Lucca

Abstract: The paper presents the results of an ambient vibration monitoring campaign conducted on so-called "Clock Tower" (Torre delle Ore), one the best known and most visited monuments in the historic centre of Lucca. The vibrations of the tower were continuously monitored from November 2017 to March 2018 using high-sensitivity instrumentation. In particular, four seismic stations provided by the Istituto Nazionale di Geofisica e Vulcanologia and two three-axial accelerometers developed by AGI S.r.l., spin-off of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 39 publications
(46 reference statements)
4
26
0
Order By: Relevance
“…In particular, the vibrations of two historic masonry towers were measured, the San Frediano Cathedral bell tower and the Clock Tower. Similar experiments on analogous structures date back to 2010, and the authors refer to Azzara et al (2019a) for an exhaustive report of the existing literature. The experiment presented herein possesses two-fold novelty: direct comparison of the results obtained on two similar structures in the same historic center, as well as the use, on both the towers, of two different high-sensitivity measurement devices.…”
Section: Introductionmentioning
confidence: 78%
“…In particular, the vibrations of two historic masonry towers were measured, the San Frediano Cathedral bell tower and the Clock Tower. Similar experiments on analogous structures date back to 2010, and the authors refer to Azzara et al (2019a) for an exhaustive report of the existing literature. The experiment presented herein possesses two-fold novelty: direct comparison of the results obtained on two similar structures in the same historic center, as well as the use, on both the towers, of two different high-sensitivity measurement devices.…”
Section: Introductionmentioning
confidence: 78%
“…The SI collects 13 contributions of high scientific quality. In particular, the first paper by Azzara et al (2020) presents the results of a continuous monitoring performed on "Torre delle Ore" located in the historic center of Lucca (Italy). While the measured vibration level was generally very low, the availability of two different types of highly sensitive and accurate instruments allowed the research group to follow the dynamic behavior of the tower during the entire monitoring period, providing moreover the cross-validation of the results.…”
Section: Structural Health Monitoring Of Architectural Heritage: From the Past To The Future Advancesmentioning
confidence: 99%
“…The aim was to compare the vault dynamic behavior in the damaged and strengthened state. Temperature changes were not considered because, for massive structures as that under consideration, the average temperature is almost constant during the different seasonal conditions as was reported in Lorenzoni et al 21 and Azzara et al 22 where it was shown that the frequencies variations due to temperature variations are of the order of 2%.…”
Section: Instrumentation and Sensors Configurationmentioning
confidence: 99%